Auditoría financiera y su incidencia en el rendimiento económico de la estación de servicios del sindicato de choferes profesionales del cantón Quevedo, año 2014 - Ayora Sánchez, Roxanna Maritza (2015)
Currently the service stations are entities that provide services to the public where there is also a high level of competition which affected fuel sales to customers and must somehow raise new strategies that result in a high level of economic performance in the Service Station Union of Professional Drivers Canton Quevedo research where I find that there is little training for employees of the company because of the duplication of work in sales took place that exists overwork on days off from the customers, I can also detect that there is a delay in payments to employees, this future cause there is a loss of employees to the company, you can also say that there is no adequate control in the United Financial cash count like this at a time can cause a low performance in the liquidity of the entity which is not convenient, to reach the final stage of the audit that we are governed present rules and legal principles in this way to establish and to issue a relevant opinion of the situation that is occurring in the state, the financial analysis of the company and comments on the financial statements was made to issue a final report and can say that the service station is an entity like others that governing certain policy according to their level of work, it is of utmost importance that the entity accepts certain recommendations in this way their work performance with employees, managers, accounting assistants, it is an appropriate extension and require each staff responsible each area fulfill their job duties and that every employer responsible for the workplace as well as accounting assistants or those working in the service station and for every shortcoming which awakens the entity seeking the most professional way strategy appropriate to raise the growth of the organization.